Burnout: A Call to Action From the AUA Workforce Workgroup. Issue 3 (4th March 2023) - Harris, Andrew M.; Teplitsky, Seth; Kraft, Kate H.; Fang, Raymond; Meeks, William; North, Amanda
Abstract : Purpose: We hypothesize burnout has failed to improve and certain demographics may be disproportionately affected. Materials and Methods: The AUA Workforce Workgroup examined work from the annual AUA Census over the past several years. Particular to this study, relevant burnout-related data were examined from the past 5 years. Results: In 2021, 36.7% of urologists reported burnout compared to 36.2% in 2016. Burnout in men decreased from 36.3% to 35.2%, but increased in women from 35.3% to 49.2%. When examined by age, the largest increases in burnout were seen in those <45 years old, increasing from 37.9% to 44.8%, followed by 45-54 years old, increasing from 43.4% to 44.6%. When asked about the effect of COVID-19 on burnout, 54% of urologists didn't feel COVID-19 impacted burnout. Beyond burnout, only 25.0% of men and 4.6% of women reported no conflict between work and personal responsibilities, while 25.7% of men and 44.7% of women resolved these conflicts in favor of work or were unable to resolve them. Of respondents, 22.5% of men and 37.1% of women were "dissatisfied" with work-life balance. Similarly, 33.6% of men reported their work schedule does not leave enough time for personal/family life, compared to 57.5% of women. Conclusions: Overall, urologists have higher burnout now when compared to 2016. The gender discrepancy has vastly widened with women experiencing burnout at an increased rate of 14% compared to 2016, while burnout in men decreased by 1%. Burnout has increased the most in those <45 years old. Further action is needed to substantiate the causes of burnout.